PHANGS-JWST first results: duration of the early phase of massive star formation in NGC 628 - Kim, Jaeyeon; Chevance, Mélanie; Kruijssen, J. M. Diederik; Barnes, Ashley T.; Bigiel, Frank; Blanc, Guillermo A.; Boquien, Médéric; Cao, Yixian; Congiu, Enrico; Dale, Daniel A.; Egorov, Oleg; Faesi, Christopher M.; et al. (The astrophysical journal. Part 2, Letters, 2023)
The earliest stages of star formation, when young stars are still deeply embedded in their natal clouds, represent a critical phase in the matter cycle between gas clouds and young stellar regions. Until now, the high-resolution infrared observations required for characterizing this heavily obscured phase (during which massive stars have formed, but optical emission is not detected) could only be obtained for a handful of the most nearby galaxies. One of the main hurdles has been the limited angular resolution of the Spitzer Space Telescope. With the revolutionary capabilities of the James Webb Space Telescope (JWST), it is now possible to investigate the matter cycle during the earliest phases of star formation as a function of the galactic environment. In this Letter, we demonstrate this by measuring the duration of the embedded phase of star formation and the implied time over which molecular clouds remain inert in the galaxy NGC 628 at a distance of 9.8 Mpc, demonstrating that the cosmic volume where this measurement can be made has increased by a factor of >100 compared to Spitzer. We show that young massive stars remain embedded for Myr ( Myr of which being heavily obscured), representing ∼20% of the total cloud lifetime. These values are in broad agreement with previous measurements in five nearby (D < 3.5 Mpc) galaxies and constitute a proof of concept for the systematic characterization of the early phase of star formation across the nearby galaxy population with the PHANGS-JWST survey.